Cultural and Religious Identity: The Development of Muslim Community at Lembah Baliem “Wamena Papua” - Helmawati Helmawati; Rudihartono Ismail (IBDA` : Jurnal Kajian Islam dan Budaya, 2021)
Islam is the second-largest religion in the world, while in Indonesia Islam is the majority religion adopted by people in Indonesia. However, in some islands such as Papua, Islam is still a minority. This study focused to describe cultural and religious identity especially the Muslim community at Lembah Baliem “Wamena-Papua”. The data on this field research was collected by observation (participative observation) and interview. For cultural anthropology, the research phase in collecting data consisted of observation, recording, verification, and description facts of Muslim Society in Wamena. The focuses of this discussion are the history of the entrance of Muslim in Wamena, how the development of the Muslim community, and how the identity of religion and culture of Muslim community in Wamena.